Recruitment, Retention and Intervention Delivery Experiences With Hospice Family Caregivers. (April 2023) - Cruz-Oliver, Dulce M.; Milner, Gabrielle E.; Abshire Saylor, Martha; Nelson, Katie E.; Blinka, Marcela D.; Durkin, Nowella; Smith, Thomas J.; Oliver, Debra Parker
Background: Recruitment and attrition are inherently challenging issues in hospice research. We sought to describe strategies of recruitment, retention, and delivery of NOVELA (short for tele novela ), an intervention for hospice family caregivers (HFCG). Methods: Statistics were kept of every referral, consenting participant, visit session, and intervention activity. We used the Social Marketing Mix Framework to describe recruiting strategies employed and lessons learned. Results: Two hospices in the U.S. Mid-Atlantic region referred 47 HFCG and N = 20 agreed to participate, out of which 50% (N = 10) completed all 4 sessions with an average of 2.8 sessions per person, each lasting an average duration of 13.5 minutes (range 8.0-25.7). The main reason for missing a session was a patient's death (N = 8). Successful recruitment strategies employed in NOVELA included: (a) intensive start-up hospice engagement, (b) remote recruitment and delivery of NOVELA, and (c) scheduling flexibility to work around caregivers' other demands. Conclusion: The recruitment and intervention delivery had successes and challenges resulting in the identification of multiple opportunities to strengthen our strategy and inform future studies with HFCGs.